Nasopharyngeal 13-virus PCR panel for the rapid diagnosis of adenovirus corneal ulcer in an infant - Zheng Fu; Lin Yuan; Weifang Fang; Hui Yang; Xixiang Wei; Xuehua Xiao (Medicine, 2026)
Rationale: Infantile corneal ulcer is a sight-threatening emergency, with bacterial and traumatic causes being common. Adenovirus (ADV), especially species D, is an under-recognized pathogen in infants. Corneal scraping is often infeasible in this age group, necessitating alternative diagnostic approaches. Patient concerns: A 5-month-old full-term twin presented with bilateral photophobia, conjunctival redness, and mucopurulent discharge lasting 10 days. Hand-held slit-lamp examination revealed pseudomembranous conjunctivitis and bilateral shield corneal ulcers measuring 6.7 mm. Diagnoses: Corneal culture was negative, and parental consent for scraping was withheld. A nasopharyngeal swab was tested using a 13-virus multiplex real-time polymerase chain reaction panel for viruses, which detected ADV subtype D within 4 hours, confirming the diagnosis of ADV-induced keratitis. Interventions: Treatment comprised topical acyclovir eye drops (8 times/day) combined with levofloxacin gel (3 times/day), along with mechanical removal of pseudomembranes. Outcomes: Complete corneal reepithelialization was achieved within 14 days, with no residual sequelae. Lessons: Nasopharyngeal 13-virus multiplex polymerase chain reaction offers a minimally invasive, rapid, and reliable diagnostic alternative for infantile adenoviral keratitis when corneal sampling is not feasible.